Milkfish Aquaculture System Selection in Supporting Food Security via System Dynamics Simulation - Saidha Umami Suyitno (Indonesian Journal of Engineering and Technology (INAJET), 2026)
Food security related to animal protein is an important factor in supporting sustainable development, particularly through the aquaculture sector. This study aims to analyze the key factors affecting the success of milkfish aquaculture, develop a dynamic simulation model for milkfish production, and evaluate the role of the supply chain in meeting consumer demand in East Java. The research was conducted in Tambakberas Village, Cerme District, Gresik Regency, with a focus on traditional and intensive milkfish aquaculture systems. Data were collected through observation, interviews, questionnaires, and secondary data on fish production and consumption. The analysis was carried out using SEM-PLS and dynamic simulation through causal loop diagrams and stock-and-flow diagrams. The results show that milkfish production is the main factor influencing production success, with a path coefficient of 0.319, a T-statistic of 2.783, and a p-value of 0.006. The simulation results indicate that the partially intensive scenario is the most rational option because it can increase production and profit while keeping operational costs more controllable. The supply chain plays a crucial role in ensuring stock availability, smooth distribution, and stable milkfish prices.